Analisis Potensi dan Pengembangan Daya Tarik Wisata Candi Singosari Malang - Isaghoji Isaghoji; Tiktik Dewi Sartika (Journal Economic Excellence Ibnu Sina, 2025)
This research aims to analyze the potential and challenges in developing the tourist attraction of Singosari Temple in Malang, with a focus on historical, cultural and environmental aspects. Through a qualitative approach and case studies, this research identifies factors that influence tourist attractions, such as accessibility, supporting facilities, and preservation of cultural sites. The research results show that to optimize tourism potential, infrastructure improvements, wider promotion and active participation of local communities are needed in the management and preservation of temples. In addition, diversifying tourism products involving educational and cultural activities can enrich tourist experiences and increase visits. Developing educational tourism activities such as historical tours and cultural performances can add value to tourist attractions. The sustainable development strategy is expected to support the preservation of Singosari Temple and have a positive impact on the local economy and the preservation of Indonesia's cultural heritage.